2014
DOI: 10.1128/jvi.01202-14
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Links Hepatitis C Virus RNA Replication to Wild-Type PGC-1α/Liver-Specific PGC-1α Upregulation

Abstract: Hepatitis C virus (HCV) causes not only severe liver problems but also extrahepatic manifestations, such as insulin resistance (IR). Wild-type peroxisome proliferator-activated receptor gamma coactivator 1 alpha (WT-PGC-1␣) is essential in hepatic gluconeogenesis and has recently been demonstrated to link HCV infection to hepatic insulin resistance (IR). A recent study has characterized a novel human liver-specific PGC-1␣ (L-PGC-1␣) transcript, which is proposed to reflect human adaption to more complex pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The UPR serves to diminish ER stress [21]. HCV infection will lead to the accumulation of viral proteins in the ER and viral protein synthesis can lead to ER stress [48,49]. Consequences of ER stress and UPR are increased mRNA levels of GRP78 (HSPA5) that acts as an inducible chaperone in the UPR and sXBP1 activation [23].…”
Section: Discussionmentioning
confidence: 99%
“…The UPR serves to diminish ER stress [21]. HCV infection will lead to the accumulation of viral proteins in the ER and viral protein synthesis can lead to ER stress [48,49]. Consequences of ER stress and UPR are increased mRNA levels of GRP78 (HSPA5) that acts as an inducible chaperone in the UPR and sXBP1 activation [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study has reported that HCV infection induces PGC-1α expression and ER stress. Moreover, pharmacological induction of ER stress upregulates PGC-1α expression, and pharmacological inhibition of HCV-induced ER stress impairs PGC-1α upregulation (Yao et al 2014).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…The specific infectivity was calculated to evaluate the efficiency of HCV assembly36, whereas the ratio of the extracellular titer to the intracellular titer was used to evaluate the level of viral particle secretion1826. Results showed that similar to siApoE, siCiDeB significantly reduced extracellular HCV specific infectivity whereas siCD81 had no effect (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate whether CIDEB is involved in the late stage of the HCV life cycle, we calculated the specific infectivity (infectious titer divided by the HCV RNA copy number) and the ratio of the extracellular HCV titer to the intracellular HCV titer, as previously described1826. The specific infectivity was calculated to evaluate the efficiency of HCV assembly36, whereas the ratio of the extracellular titer to the intracellular titer was used to evaluate the level of viral particle secretion1826.…”
Section: Resultsmentioning
confidence: 99%